Manajemen Proyek Sistem Informasi Penyortiran Laporan Keuangan Pada Kantor Badan Keuangan Dan Aset Daerah Provinsi Sumatera Utara Berbasis WEB - Aulia Alsaf Salsabilla; Yahfizham Yahfizham (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
This research aims to develop an efficient and reliable information system for the financial report sorting process at the Office of the Provincial Financial and Asset Management Agency of North Sumatra, using a comprehensive project management approach. The research methodology involves user needs analysis, designing a responsive web-based system, development using the latest technology, and thorough testing to ensure system security and performance. The expected outcome is improved efficiency and accuracy in financial report sorting, with the potential for synergistic integration with existing systems for better public financial management in the region.